Pathogenesis of traumatic temporomandibular joint ankylosis: a narrative review. Issue 11 (November 2020) - He, Linhai; Zhang, Zhiyong; Xiao, E; He, Yang; Zhang, Yi
Objective: To comprehensively review the literature and summarize the results from human and animal studies related to the possible causes and pathogenesis of traumatic temporomandibular joint ankylosis (TMJA). Materials and Methods: The Google Scholar, Embase, and Web of Science databases were used to search for articles related to traumatic TMJA from 2011 to 2020. All articles were screened according to the inclusion and exclusion criteria, collected, and analyzed. Results: Nineteen relevant articles were collected. These articles were classified into three groups: predisposing and etiological factors, cellular studies, and molecular studies. Conclusion: The pathological mechanisms are similar between TMJA and nonunion hypertrophy. Aberrant structural and etiological factors as well as disordered cellular and molecular mechanisms might contribute to TMJA formation. Although preclinical and clinical data have provided new evidence on the pathogenesis of traumatic TMJA, the molecular mechanisms and biological events require further exploration.